Influences of Ammonium Nitrate on Growth and Inulin Content of Jerusalem Artichoke (Helianthus tuberosus L.) in Vitro - Punha, Phuangpha; Neera, Sumana; Hongpakdee, Panupon (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 3 (2019): July-September 2019DO - 10.14456/nujst.2019.27, 2019)
Jerusalem artichoke ( Helianthus tuberosus L.) consists of high inulin and fructose, useful for the pharmaceuticals and chemical industries. Therefore, previous researchers have studied on the micropropagation of Jerusalem artichoke from seeds, nodes, and young leaves; effects of sugar and plant growth regulators on culture and inulin content in Jerusalem artichoke; and microtuber propagation. However, studies on the effects of ammonium nitrate (NH 4 NO 3 ) on growth and biosynthesis of inulin in Jerusalem artichoke are scarce at present. Therefore, the objective of this work was to evaluate the effect of NH 4 NO 3 on the growth of Jerusalem artichoke and its inulin content in vitro . Auxiliary meristems from the field-grown plants were cultured on MS medium containing 0, 825, 1,650, and 3,300 mg/L NH 4 NO 3 . The inulin content of plantlets was analyzed by HPLC-RID after subculturing every 4 weeks for 5 times. The results showed that shoot length, node number, leaf number, leaf width, leaf length, fresh weight, and dry weight were maximum in 3,300 mg/L NH 4 NO 3 . While shoot number and root number were best in 1,650 mg/L NH 4 NO 3 . Furthermore, the study found maximum inulin content on MS containing 1,650 mg/L NH 4 NO 3 and higher hyperhydricity in higher concentrations of NH 4 NO 3 . Overall, MS containing 1,650 mg/L NH 4 NO 3 showed a positive effect on vegetative growth, hyperhydricity, and inulin production of Jerusalem artichoke. It can be used as an alternative approach for propagation and inulin production from Jerusalem artichoke. Keywords: Ammonium nitrate, HPLC – RID, Inulin, In vitro , Jerusalem artichoke